Leave No One Behind: Using Flow Learning to Increase Outdoor Recreation Opportunities for People of All Abilities. - Leo, Jennifer; Mustafa, Hamid; Mourton, Niamh-Elizabeth; O'connor, Ann (Palaestra, 2018)
The UN's Sustainable Development Goals (SDGs) promote sustainable development, including access to nature. Despite benefits associated with outdoor engagement, people with disabilities are less likely to have access. The Flow Learning framework has potential to promote outdoor engagement for people with disabilities. Flow Learning involves a sequence of activities to introduce and engage learners with nature. This paper uses a case example to present a potential applications of Flow Learning to develop meaningful outdoor activities for adults with disabilities (aged 18 to 25 years) within the context of the SDGs. Discussion focuses on how Flow Learning is useful to develop structured programming that stimulates outdoor appreciation among people with disabilities.